Studi Literatur: Artificial Intelligence Dalam Audit - Veren Putri Shamaya; Sabrina Nova Ashara; Achmad Sofyan; Salsabila Aprilia; Arswarani Leonica; Tri Ratnawati (JURNAL RISET MANAJEMEN DAN EKONOMI (JRIME), 2023)
The purpose of this study is to find out how the influence, role, and progress of Artificial Intelligence in Auditing. The approach in this study uses a type of research in the form of a literature study with data collection methods in the form of library data that has been selected, searched and analyzed. Based on the research results, it is known that Artificial Intelligence has quite a significant influence on the positive and negative sides. Artificial Intelligence also provides a useful role in auditing developments in the present and in the future, although in practice Artificial Intelligence still has many weaknesses because auditing still requires an auditor's assessment.